Revision of the genus Actinostella (Cnidaria: Actiniaria: Actinioidea) from tropical and subtropical western Atlantic and eastern Pacific: redescriptions and synonymies - Barragan, Yamalí (2024)
Sea anemone species of the genus Actinostella live in tropical and subtropical shallow waters. They are characterized by having a marginal ruff harboring zooxanthellae that expands during the day and retracts at night, allowing the anemone to catch prey with the tentacles. Currently, 10 or 11 species are considered valid depending on the author; however, most species within the genus were described in the 1800s or in early 1900s and, thus, most descriptions are incomplete by modern standards. In addition, several species of Actinostella have reported wide geographical distributions. We evaluate the morphology of newly collected and type material to assess potential synonymies and geographical distributions; we perform phylogenetic analysis using five standard molecular rDNA markers for sea anemones to corroborate our morphological results and to investigate the phylogenetic relationships of Actinostella, other actinioideans, and those Actinostella species present in the eastern Pacific and western Atlantic tropical region. Based on morphological and cnida differences, we find six species of Actinostella valid. We redescribe A. bradleyi, A. californica, A. digitata, and A. flosculifera and synonymize A. californica pro parte (Pacific specimens with four cycles of mesenteries and p-mastigophores A in the marginal ruff) with A. bradleyi (found in the Panamanian and Mexican Pacific and the Gulf of California). We also find that A. ornata does not belong within Actinostella. We discuss the membership of Actinostella, including species of the genus Phyllactis, and synonymize Phyllactis with Actinostella. We propose that the combination of the presence of p-mastigophores A in the marginal ruff and the arrangement and fertility of mesenteries are diagnostic characteristics to differentiate species of Actinostella from the American coasts. Finally, our phylogenetic analyses based on rDNA markers differentiated between the western Atlantic and eastern Pacific species but lacked support and resolution to elucidate relationships within species in the eastern Pacific.